Perceptions of Health and Safety among Immigrant Latino/a Dairy Workers in the U.S. - Menger, Lauren M.; Pezzutti, Florencia; Tellechea, Teresa; Stallones, Lorann; Rosecrance, John; Roman-Muniz, Ivette Noami (Frontiers in Public Health, 2016)
The U.S. dairy industry is increasingly relying on an immigrant workforce to help meet growing demands. Due to scant research, little is known about the factors related to workplace safety among this occupational group. The purpose of this study was to identify dairy worker perceptions of the barriers to and facilitators for enhancing workplace safety. Focus groups (FG) were conducted with 44 immigrant Latino/a workers from 2 dairies in South Dakota and 1 dairy in Colorado to gain firsthand insights into their work experiences. Interviews were conducted in Spanish, audio recorded, transcribed, and translated into English. Results were analyzed through a two-step qualitative coding process. The Contributing Factors in Accident Causation model was used as a guiding framework. Promising points of intervention identified were related to the workers, the work itself, the physical environment, equipment issues, the social–psychological environment, and management/organizational factors. Suggestions for how to improve safety outcomes in the dairy industry are provided. It is likely that the dairy industry will continue to employ a growing number of immigrant workers. Therefore, these findings have significant implications that can be used to guide the development of culturally congruent policies and practices.